Antigen otoxicity of Agaricus blazei mushroom organic and aqueous extracts in chromosomal aberration and cytokinesis block micronucleus assays in CHO-k1 and HTC cells - Bellini, M. F.; Angeli, JPF; Matuo, R.; Terezan, A. P.; Ribeiro, Lúcia Regina [UNESP]; Mantovani, M. S. (Elsevier B.V., 2006)
Agaricus blazei (Ab) has become popularly known for its medicinal properties. Scientifically, it has been tested with regard to its capacity to protect genetic material against damage. We examined different organic extracts (methanolic extract-ME, hexanic extract-HE and n-butanolic extract-BE) and an aqueous extract (AE) of Ab, for their capacity to induce DNA damage as well as for their protective effect. Genetic damage was determined by the chromosomal aberration assay (CA) in CHO-k1 cells for all extracts and the cytokinesis block micronucleus assay (CBMN) in non drug-metabolizing (CHO-k1) and drug-metabolizing (HTC) cell lines for extract BE only. The extracts did not show clastogenicity but showed anticlastogenicity. The greatest percent reduction obtained were with BE (105%) and AE (126%) treatments in CA. BE treatment did not display genotoxicity in CHO-k1, but was genotoxic in HTC. However, BE was shown to be antigenotoxic causing decreased micronucleus frequency in HTC and CHO-k1 cells. These results suggest that all the extracts contained protective substances, but in some cases they could show a genotoxic effect with regard to metabolism. Therefore, these findings warrant caution in the use of this mushroom by the population. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: antigenotoxicity; Agaricus blazei; drug metabolism; HTC cells; CHO-k1 cells; chromosomal aberration assay